2007
DOI: 10.2500/aap.2007.28.2939
|View full text |Cite
|
Sign up to set email alerts
|

Lung function, asthma paradox, atopy, and risk factors in Mexican spirometry-diagnosed asthmatic patients

Abstract: Despite long-term studies, still not much is known about the asthma triggering factors and its sometimes controversial results. Probably one of the major problems of controversy is the lack of specific and accurate diagnosis of this disease. The aim of this study was to assess lung function, atopy, and environmental factors in spirometry-diagnosed asthmatic patients. Time series of daily counts of hospital emergency admissions were constructed for known asthmatic subjects. Spirometry, chest radiograph, arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…For example, research done by Recio-Vega et al 20 in Mexico found that more than one third of patients with newly diagnosed asthma had a positive allergy skin test response. 20 Our study showed that less than 15% of Mexican American children had received an allergy diagnosis, despite research that shows Mexican Americans have a higher prevalence of both asthma and hay fever than their counterparts living in Mexico. 21 Our results show children who used a physician's office as their usual source of care were more likely to respond that they were given a diagnosis of allergy than children using other sources of care.…”
Section: Disparities In Allergy Diagnoses and Lack Of Testingmentioning
confidence: 54%
“…For example, research done by Recio-Vega et al 20 in Mexico found that more than one third of patients with newly diagnosed asthma had a positive allergy skin test response. 20 Our study showed that less than 15% of Mexican American children had received an allergy diagnosis, despite research that shows Mexican Americans have a higher prevalence of both asthma and hay fever than their counterparts living in Mexico. 21 Our results show children who used a physician's office as their usual source of care were more likely to respond that they were given a diagnosis of allergy than children using other sources of care.…”
Section: Disparities In Allergy Diagnoses and Lack Of Testingmentioning
confidence: 54%